2015
DOI: 10.1186/s12933-015-0262-8
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase (HDAC) inhibition improves myocardial function and prevents cardiac remodeling in diabetic mice

Abstract: BackgroundRecent evidence indicates that inhibition of histone deacetylase (HDAC) protects the heart against myocardial injury and stimulates endogenous angiomyogenesis. However, it remains unknown whether HDAC inhibition produces the protective effect in the diabetic heart. We sought to determine whether HDAC inhibition preserves cardiac performance and suppresses cardiac remodeling in diabetic cardiomyopathy.MethodsAdult ICR mice received an intraperitoneal injection of either streptozotocin (STZ, 200 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
110
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 57 publications
9
110
1
1
Order By: Relevance
“…Class I, II, and IV HDACs are zinc-dependent enzymes, whereas class III HDACs, which are also known as sirtuins, require nicotinamide adenine dinucleotide (NAD + ) for catalytic activity (13). Recent studies have shown that activation of HDACs was associated with DCM since total HDAC inhibition attenuated diabetes-induced cardiac injury in the STZ-induced diabetic animal models (14, 15). In these two studies, it is unclear which specific HDAC really involves in the pathogenesis of DCM because they only used non-specific HDAC inhibitor to inhibit total HDAC activity.…”
Section: Introductionmentioning
confidence: 99%
“…Class I, II, and IV HDACs are zinc-dependent enzymes, whereas class III HDACs, which are also known as sirtuins, require nicotinamide adenine dinucleotide (NAD + ) for catalytic activity (13). Recent studies have shown that activation of HDACs was associated with DCM since total HDAC inhibition attenuated diabetes-induced cardiac injury in the STZ-induced diabetic animal models (14, 15). In these two studies, it is unclear which specific HDAC really involves in the pathogenesis of DCM because they only used non-specific HDAC inhibitor to inhibit total HDAC activity.…”
Section: Introductionmentioning
confidence: 99%
“…As there is evidence of genetic association between diabetes and HDACs, treatment with HDACi exerts a reduction in glomerular endothelial markers expression, which demonstrates the anti-angiogenic beneit [83]. This efect seems to be opposite when it applies to the diabetic heart failure model, as another HDACi sodium butyrate exerts improved cardiac functions and increased microvessel density within the diabetic myocardium [84]. Moreover, HDACi also modulates cardiac peroxisome proliferator-activated receptors (PPARs) and faty acid metabolism in diabetic cardiomyopathy [85].…”
Section: Hdacs Role In Angiogenesis In Diabetesmentioning
confidence: 98%
“…The previously described Valproic Acid is also a short-chain fatty acid HDACi [30]. Treatment with sodium butyrate or valproic acid inhibited cardiac hypertrophy and fibrosis and increased systolic function in pre-clinical rodent models of heart failure [46,51].…”
Section: Bioactive Hdacimentioning
confidence: 99%